Comparison Between Three Rotary Files on Quality of Obturation and Instrumentation Time in Primary Teeth − A Double Blinded Randomized Controlled Trial - Sofiya Juliet; Ganesh Jeevanandan; Lavanya Govindaraju; Vignesh Ravindran; Erulappan Muthuganapathy Subramanian (Wolters Kluwer Medknow Publications, 2020)
Introduction: There are many available Nickel Titanium (Ni-Ti) rotary systems that are used for canal cleaning and shaping of the permanent teeth. The new emerging concept in pediatric dentistry is the use of rotary files for canal instrumentation in primary teeth. In literature, there are no clinical studies comparing three different rotary systems in primary teeth. The aim of this study was to compare and evaluate the quality of obturation and instrumentation time using three rotary file systems in primary mandibular molars. Materials and Methods: A total of 45 primary mandibular molars were included in the study and were randomly allotted to one of the three groups. Group 1: ProTaper files; Group 2 Kedo-S files and Group 3: RaCe files. Standardized digital radiographs were taken to the assess quality of obturation as underfill, optimal fill and overfill. Statistical analysis was done using SPSS software version 17.0. An intergroup comparison of the quality of obturation and instrumentation time was done using Chi-square test and ANOVA with the level of significance set at 0.05. Results: No significant difference was observed in the quality of obturation among the three groups (P = 0.661). However, a statistically significant was noted in the instrumentation time among the groups (P < 0.05). In Kedo-S files group 80% of the teeth were optimally filled followed by 60% in ProTaper files and 46.67 % in RaCe files group. The instrumentation time was least in RaCe files 31.67 secs followed by ProTaper files 45.93 secs and Kedo-S (78.53 secs). Conclusion: No significant difference was noted with respect to quality of obturation using S2 ProTaper files, Kedo-S files and RaCe files in primary teeth. There was a significant difference in instrumentation time among the three groups with least working time with RaCe files.